PowerPoint Presentation Technology and the Dynamics of Teaching - Craig, Russell J.; Amernic, Joel H. (Innovative higher education, 2006)
This article presents a wide-ranging analysis of the use of PowerPoint technology in higher education. It addresses four overlapping issues. Has PowerPoint led to more effective learning? What impact has PowerPoint had on the dynamics of classrooms? What are some important aspects of the culture that accompanies PowerPoint? How has PowerPoint affected orality, visuality and literacy? The purpose of our article is to stimulate beneficial conversations about a prevalent educational software technology.